Impact of Cell Size and Format on External Short Circuit Behavior of Lithium-Ion Cells at Varying Cooling Conditions: Modeling and Simulation. Issue 1 (3rd October 2019) - Rheinfeld, Alexander; Sturm, Johannes; Frank, Alexander; Kosch, Stephan; Erhard, Simon V.; Jossen, Andreas
Abstract : A multidimensional multiphysics model is presented to describe the external short circuit behavior of lithium-ion cells of various formats and sizes at different convective cooling conditions. For this purpose, a previously published homogenized physical-chemical model of the external short circuit behavior of a small-sized lithium-ion cell was combined with an electrical and a thermal model to describe in-plane inhomogeneities in current density and heat generation rate throughout the electrodes, together with the resulting temperature distribution within the cell's jelly roll or electrode stack. With the investigated cylindrical, prismatic, and pouch-type cell formats combined with cell capacities ranging from consumer-sized to automotive applications, a comprehensive cell design study is presented during external short circuits. The investigated surface and tab cooling strategies reveal a limited cooling capability of each cell format and size, which seems to be defined by the ratio of cooled surface area to electrode area as well as the thermal resistivity of the respective cell geometry. The simulation results show that only thin cells with a large ratio of cooling surface to electrode area can be physically maintained within an uncritical operating window of cell temperature and state of charge in case a low-resistance external short circuit is applied.